Collecting qualitative research data on health seeking behaviour of Peninsular Malaysia’s aboriginal people - W., Vivien C. Yew (Faculty of Social Sciences and Humanities, UKM,Bangi, 2015)
Qualitative research is an appropriate method for obtaining insight into situations and problems when a researcher has little knowledge concerning a research question. Applying to a cultural context of health and illness, this method is commonly used for providing in-depth description of cultural beliefs and local knowledge related to health issues, or for exploring the reasons for certain health seeking behaviours adopted by research informants. This study provides a pragmatic approach in examining the various stages of a qualitative data collection process pertaining to the aboriginal people or the Orang Asli of Malaysia. The research was conducted in three selected Orang Asli villages in the states of Selangor, Pahang and Perak of Peninsular Malaysia. A total of 55 in-depth interviews were successfully recorded during the fieldwork duration of July 2013 to January 2015. Employing face-to-face in-depth interviews and non-participant observations, the research collected data with regard to health and health seeking behaviors of the Orang Asli. The primary data were used to illustrate how various qualitative data collection methods could be used to facilitate the data collection process. Several concepts employed in data collection such as theoretical sensitivity, triangulation and verification were also elaborated.